Effect of plasticizer on physical and mechanical properties of ldpe/sago starch blend - Kormin, S.; Kormin, F.; Beg, M. D. H. (IOP Publishing, 2019)
Starch-based polymeric materials offer a renewable, economical alternative to existing petroleum based, non-renewable or costly polymeric materials. The aim of this study is to develop degradable starch-low density polyethylene (LDPE) composites with enhanced mechanical properties. This research studies the effect of different kind of plasticizer. The compounding of the LDPE with sago starch was performed via a twin screw extruder followed by injection molding. Studies on their physical, mechanical of each formulation were carried out by density, melt flow index (MFI), tensile, flexural, impact. The presence of high starch contents had an adverse effect on the mechanical properties of LDPE/starch blends. However, the addition of compatibilizer or plasticizer improved the interfacial adhesion between the two materials, hence, improved the tensile properties of the blends. After using the proper composition and processing condition, mechanical properties of plasticized LDPE/SS blend are significantly higher than those of the unplasticized LDPE/SS blend with the same starch contents.